The Relationship Between Russian Kindergarteners’ Play and Executive Functions: Validating the Play Observed Behaviors Scale - Veraksa, Aleksander; Bukhalenkova, Daria; Almazova, Olga; Sukhikh, Vera; Colliver, Yeshe (Frontiers in Psychology, 2022)
Background: Young children’s play is theorized to develop executive functions, skills strongly predictive of many later advantages. The current study sought to validate a practicably short play behavior survey for kindergarten teachers (N = 18) and compare the reported behaviors to the executive functions (EFs) of their 443 Russian kindergarteners (Mage = 78.6 months; SD = 4.04). Research Findings: The factor model with satisfactory construct validity and internal consistency included three factors: leadership, play preferences and rule conformity. Analyses provide partial support for Vygotsky’s theory that play supports EF development, but particular behaviors were related to different EF components. However, kindergarteners exhibiting more leadership, preferences and conformity overall rated higher on most EF components. Practice and Policy: These findings do not support the theory that play skills improve unidirectionally with age and EFs, suggesting particular profiles of types of players and complex changes with age. The play behavior survey may be a practicable way to trace different profiles across the early years.